The Assistance Quality, Farmer Characteristics, and Farmer Motivation Towards the Performance of Farmer Groups - Sulaiman Sulaiman; Asri Asri; M. Saleh S. Ali (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
The agricultural sector is vital in national economic development and the large contribution of farmer groups in increasing the effectiveness of farming businesses. However, the performance of farmer groups is still influenced by various factors, such as the quality of mentoring, farmer characteristics, and farmer motivation, which are not fully understood in depth, especially in Pitu Riawa District, Sidrap Regency. Therefore, this research aims to was to examine how assistance quality, farmer characteristics, and farmer motivation impact the performance of farmer groups in Pitu Riawa District, Sidrap South Sulawesi. The sampling method employed in this research was non-probability sampling using saturated sampling, which involved all farmers in 300 farmer groups from Pitu Riawa sub-district, Sidrap district. Data for this study were collected through a questionnaire and analyzed using Partial Least Square (PLS) software. The findings revealed that both the quality of assistants and farmer characteristics had a positive and significant influence on farmer motivation. Additionally, the quality of assistants and farmer characteristics also had a positive and significant impact on farmer group performance. However, farmer motivation only had a positive but insignificant effect on performance. Furthermore, the quality of assistants positively and significantly influenced farmer group performance through farmer motivation, whereas farmer characteristics had a positive but insignificant effect on farmer group performance through farmer motivation. The implications of the results of this study indicate that improving the quality of assistants and strengthening farmer characteristics are the main keys in encouraging farmer motivation and improving farmer group performance. Hence, it is recommended that farmer empowerment programs focus more on improving the competence of facilitators and developing the capacity of farmers through continuous training and coaching.